Pengaruh Lingkungan Kerja, Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Perintis Perkasa Medan - Yovie Ernanda; Wandy Halim; Michael Riady; Edisah Putra Nainggolan (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to test and analyze the effect of work environment, work motivation and work discipline on employee performance of PT Perintis Perkasa Medan. The research method used in this study uses quantitative research methods with descriptive quantitative research types that are explanatory research. The population of this study were employees at PT Perintis Perkasa Medan totaling 73 people, the sample of this study were 73 respondents. The data analysis method used is multiple linear regression. The results of the f test research where f count 170.569> f table 2.74 with a significant level <0.05 shows simultaneously Work Environment, Work Motivation and Work Discipline simultaneously have a significant influence on the Performance of Employees of PT. Perintis Perkasa Medan. The results of the t test research where the work environment has a positive and significant influence on the performance of employees of PT Perintis Perkasa Medan, work motivation has a positive and significant influence on the performance of employees of PT Perintis Perkasa Medan and work discipline has a positive and significant influence on the performance of employees of PT Perintis Perkasa Medan. The results of the coefficient of determination analysis obtained Adjusted R2 value of 0.876, meaning that the variation of Work Environment, Work Motivation and Work Discipline variables is 87.6%, while the remaining 12.4% is explained by other variables. Keywords: Work Environment, Work Motivation, Work Discipline, Employee Performance